The Impact of Trust Factors in an E-Commerce Transactions (Security and Privacy) Environment on Saudis Consumers’ Behaviour in Saudi Arabia - Haya ALSHEHRI (Communications of International Proceedings, 2023)
E-Commerce Business-to-Consumer (B2C) is essential for businesses today, although can hold many challenges such as security and privacy. The present research aims to uncover the actual interest of developing a project in the area of E-Commerce within a developing country, Saudi Arabia (SA), and Saudi customers regarding the impact of trust factors on E-Commerce payment transactions and the protection of customers’ privacy of personal information. This research focuses on Saudis’ consumer behaviour, exploring the changes within the past 8 years in aspects such as trust, security, and privacy that might affect Saudis in their decision to engage with E-Commerce without any hesitation. For this study, it purposes to collect data from SA to to draw a comparison with respect to results from the past outcomes 8 years ago, which will now include a new model with a new outcome, thus allowing this model to be used to improve B2C in SA. The study adopts a qualitative approach via semi-structured interviews to enable in-depth information. As the nature of qualitative research is iterative and growing, interim discoveries can be used to apprise continuing data collection analysis. Most of the approaches as of recently utilise models of E-Commerce in developed countries, highlighting the importance of this model as it collects data from SA, a developing country of which the customer base is rapidly growing in E-Commerce field. The outcome of this research will be published in second stage of this study.